Sejarah Kodifikasi Ilmu Qira’at dan Urgensinya Sebagai Warisan Bacaan Al-Qur’an Yang Mutawatir - Ikma Pradesta Putra Prayitna; Annisa Berliana; Yuli Yanti; Romlah Widayati (Jurnal test, 2024)
The Qur’an was revealed in the midst of an Arab society with its own culture and language. The heterogeneous conditions of the society cause linguistic differences and dialectics. The problem that arises is the differentiation of abilities between individuals and groups related to language, especially Fusha Arabic. For this reason, the Prophet said, “Verily, the Qur’an was revealed with seven letters, so read the easiest”. One view of the meaning of the Hadith is that the Qur’an was revealed with seven languages and dialectical varieties. This research uses a qualitative method with the type of revelation text study included in the literature study. The result of the research is that qira’at began to be organized into a discipline by Abu Ubaid al-Qasim by compiling the work of the book of qira’at, which collected twenty-five qira’at. The differences in qira'at are divided into two, namely uhsuliyah rules; standardized rules in the reading of each Imam and farsy al-huruf; differences in typical readings that exist in each Imam and narrator. The difference in qira’at in farsy al-huruf mostly gives implications in interpretation. Suggestions for future research can examine aspects of qira’at in more depth through historical aspects and implications of interpretation.